Raising private finance for public infrastructure in Sub-Saharan Africa: Exploring Infrastructure Mutual Funds and Islamic Finance - Arimoro, Augustine Edobor; Elgujja, Abba Amsami (Institut Agama Islam Negeri Kendari, 2022)
Sub-Saharan Africa (SSA) lags other regions of the world as far as critical infrastructure is concerned. Even though the region has great potential, the governments in the region are constrained by budget deficits and competing demands for state resources. With limited access to foreign finance for private sector-led infrastructure procurement in most economies in SSA, this article examines how innovative financial products can be developed to unlock domestic finance for infrastructure. The article adopts a law and development approach. The article recommends the development of infrastructure mutual funds and Islamic finance as alternative sources for infrastructure finance in SSA. This recommendation is based on Prof YS Lee's adaptability to socioeconomic conditions theory.